Model independent bounds on heavy sterile neutrinos from the angular distribution of B → D* ℓν decays - Florian U. Bernlochner; Marco Fedele; Tim Kretz; Ulrich Nierste; Markus T. Prim (Journal of High Energy Physics)
Abstract In this paper we study the bounds that can be inferred on New Physics couplings to heavy sterile neutrinos N from the recent measurements performed by the Belle collaboration of the angular analysis of B → D ∗ ℓ ν ¯ ℓ $$ B→ D^{*}\ell {\overline{ν}}_{\ell } $$ decays, with ℓ = e, μ. Indeed, a sterile neutrino N may lead to competing B → D ∗ ℓ N ¯ $$ B→ D^{*}\ell \overline{N} $$ decays and Belle might have measured an incoherent sum of these two independent channels. After reviewing the theoretical formalism required to describe this phenomenon in full generality, we first perform a bump hunt in the M miss 2 $$ M_{miss}^2 $$ Belle distribution to search for evidences of an additional massive neutrino. We found in such a way a small hint at M miss 2 $$ M_{miss}^2 $$ ∼ (354 MeV)2. However, the Belle angular analysis is sensitive to N masses up to O $$ \mathcal{O} $$ (50 MeV), preventing us to further inspect this hint. Nevertheless, we study the potential impact of this additional channel in the allowed mass range on the measured angular distributions and extract model-independent bounds on the new-physics couplings which could mediate such an interaction. In particular, in the mass window here inspected, we obtain the most stringent bounds for vector and left-handed scalar operators to date.